Macroeconomic effects of looming policy shifts: Non-falsified expectations and Peso problems - Jouko Vilmunen (Bank of Finland, 1998)
Using a standard model as a basis, we analyse the rational expectations macroeconomic equilibrium for an open economy with flexible exchange rates, in which expectations are affected by a percieved possibility of discrete shifts in monetary policy.These discrete shifts are modelled as possible jumps in the money supply process, which is otherwise a smooth random walk.Two such jump models are analysed.In equilibrium, the distribution of endogenous variables is (apparently systematically) affected by peso problems (premia), which reflect distributional peculiarities associated with expectations of possible future policy shifts.It turns out that the macroeconomic effects of peso premia accord closely with intuition regarding the effects of poor credibility of a policy regime: the output gap widens; the levels of real interest rates and domestic prices rise; and the domestic currency appreciates in real terms due to anticipated expansionary shifts in the money supply.Moreover, the key macro-aggregates become more volitile. The effects of peso premia on the nominal interest rate and the exchange rate turn out to be ambiguous.
URN:NBN:fi:bof-20140807438
Keywords: 330; poisson process; policy shifts; peso problem; rational expectations